A Study to Assess the Effectiveness of Planned Teaching Programme on Knowledge regarding Management of Hypertension among Care Taker of HypertensivePatients in SAIMS Hospital, Indore (International Journal of Food and Nutritional Sciences, 2022)
A quantitative pre experimental study was conducted to evaluate the effectiveness of knowledge regarding management of hypertension. Objectives of the study were to assess the pre test knowledge regarding management of hypertension, to assess the effectiveness of planned teaching programme regarding management of hypertension and to find out the association between knowledge scores with selected demographical variables. The study conducted with pre experimental one group pre test and post test design, with non probability convenient sampling technique. There were significant increase in the mean post test knowledge scores of the care takers of hypertensive patients regarding management of hypertension after implementation of PTP in comparison with the mean pre test knowledge scores and there was a no significant association between pre test knowledge score with selected demographic variables.